Pengaruh Bermain Peran/Drama Terhadap Perkembangan Perilaku Sosial Pada Anak Prasekolah (4-6 Tahun) - Martina Sidang P., - (2010)
The main problem is mostly happened in preschool children is the lateness in the development of social behaviors. This disorder could happen because of some factors that influence it. One of the factor is lack of playing stimulation given at preschool children. The objective of this study was to analyze the effect of role playing/theater to the development of social behaviors in preschool children. This research use a pre-experimental one-group pre-post test design. Populations were the student of a class Dharmawanita Kindergarten, Kepuhrejo, Takeran, Magetan. The sample based on inclusion criteria is using purposive sampling which is consist of 16 respondents, taken according to the inclusion criteria. Data were collected by observation. Then, data were tabulated by Wilcoxon Signed Rank Test with significance level 0.05. The results showed that role playing/theater affect the development of the social behaviors p=0.000 (p<0.05). It can be conclude that role playing/theater has significantly effect the development of the preschool children’s social behavior. Important to do further research about role playing to the development of language in preschool children